WISATA PEMANCINGAN DI KABUPATEN KUBU RAYA - Nugraha, Rafly Ihza; Affrilyno, Affrilyno; Muazir, Syaiful (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Fishing tourism is a place to accommodate fans of fishing activities. With fishing tours, fishing enthusiasts can express their hobbies in the places that have been provided. Fishing tourism centers not only have fishing ponds, but also provide various kinds of existing facilities. Kubu Raya Regency is one of the largest districts in West Kalimantan Province. Kubu Raya Regency has many kinds of potential that can be developed, one of which is fisheries. The fishery in Kubu Raya is one of the largest in West Kalimantan. Seeing the potential of Kubu Raya Regency in the form of fisheries that can be further developed, the location of the design of the fishing tourism center is in Kubu Raya Regency. This fishing tourism center is expected to accommodate fishing enthusiasts and optimize tourism and natural potential as well as increase the economic growth of Kubu Raya Regency. The design of this fishing tour uses five design methods, namely the initial stage, preparation, making proposals, evaluation and action. This design produces a fishing tourism design in which there are 4 building masses with different functions, namely restaurants, cafe, prayer rooms, and management buildings and can work together with local residents by providing facilities in the form of a pier.